Design of intelligent dual FSR sensor-based rheologiometer for viscoelastic quality control - Alrewaished Ahmed Abdulsalam A (2023)
This project will be focused on design of intelligent dual FSR sensor-based rheologiometer for viscoelastic quality control. In this paper, it will expose on how the testing of three different type of plastic materials gave the different results based on it's strain and stress. The outcome of this project will be determined whether this system can be used into production line or in real world.